The influence of transparency on Muzakki's interest in giving Zakat to Baznas Deli Serdang - Hairuna, Fadila; Syahrul Amsari (SEAN Institute, 2024)
This research aims to investigate the impact of transparency on the interest of muzakki to donate zakat to the National Zakat Amil Body (Baznas) Deli Serdang. The addressed issue reflects the need to comprehend the extent to which transparency in zakat management can influence the community's interest (muzakki) in contributing zakat. The study was conducted in the complex of Deli Serdang Regional Government, Jalan Karya Agung No.4, Tj. Garbus Satu, Lubuk Pakam District, Deli Serdang Regency, North Sumatra. Utilizing a quantitative method, the research involved 51 respondents who responded to a distributed questionnaire. Data analysis employed a simple linear regression test using statistical software (SPSS). Preliminary results indicate the rejection of the null hypothesis, indicating the influence of transparency on the interest of muzakki to donate zakat to Baznas Deli Serdang. Despite statistical significance, the relationship between the variables was found to be low, suggesting that other factors may play a role in influencing muzakki's interest. This conclusion provides initial insights into the importance of transparency in enhancing community participation in zakat activities. Further research is expected to explore additional variables that may more deeply impact muzakki's interest.